Does market integration promote to firm information efficiency? Empirical evidence for Malaysia listed firms - Tai, Kui Guan; Hooy, Chee Wooi (Penerbit Universiti Kebangsaan Malaysia, 2017)
Global information transmits fast into share price if a company is highly integrated with the world market. On the contrary, a segmented firm that has higher integration with local market is expected to have slow response to global information. This paper tested whether the above is true for listed firms in Malaysia, a fast-emerging market that consists of large pool of both integrated and segmented firms. The degree of market integration is measured by the variance ratios approach proposed by Akdogan (1997) while informational efficiency is captured by the price delay measure suggested by Hou and Moskowitz (2005). We analyzed a panel of 265 firms from 1995 to 2010 and found that firms with higher integration with world market have better global information efficiency while segmented firms were significantly slow to impound global news. Our results are robust to the choice of different proxies of informational efficiency as well as different control variables and a variety of alternative regression specifications. Our findings imply that the policymakers should consider further liberalize the Malaysian stock market to increase its transparency and reduce information barriers so that information efficiency can be improved and contribute to economic growth agenda.